Ressentimento: (im)possibilidade de elaboração - Leitão, Luiza Maria Carneiro de Carvalho (2007)
2007. This thesis is the result of the great interest awaken in me for resentment, always so present in the clinical practice, and of the need to extend my understanding of the theme. Bearing in mind the small prominence the theme has seen in the psychoanalytical field, I have made my way towards literature and philosophy and made use of them to build a wider frame. This paper aims at showing some ways our patients find to deal with the affective constellation called resentment, and point out that the possibility of a healthy outcome such as literary creation is not always open, but that through psychoanalytical work it is possible to remove the subject from the position of a victim and make him assume his position as a subject. I have worked with the hypothesis that resentment is the result of a narcissistic failure that happens at the encounter of a certain baby with a little favorable environment. From this encounter would result a frail self, ill prepared to face situations that are considered humiliating or highly offensive by this subject. This research results in the conception of resentment as a primary defense used every time the subject feels attacked in his narcissism, so frailly composed. Yet through repetition, resentment is used as a defense, even though it is a little appropriate defense and results in false gains